Dietary lipids are largely deposited in skin and rapidly affect insulating properties - Nick Riley; Ildiko Kasza; Isabel D. K. Hermsmeyer; Michaela E. Trautman; Greg Barrett-Wilt; Raghav Jain; Judith A. Simcox; Chi-Liang E. Yen; Ormond A. MacDougald; Dudley W. Lamming; Caroline M. Alexander (Nature Communications)
Abstract Skin is a regulatory hub for energy expenditure and metabolism, and alteration of lipid metabolism enzymes in skin impacts thermogenesis and obesogenesis in mice. Here we show that thermal properties of skin are highly reactive to diet: within three days, a high fat diet reduces heat transfer through skin. In contrast, a dietary manipulation that prevents obesity accelerates energy loss through skins. We find that skin is the largest target for dietary fat delivery, and that dietary triglyceride is assimilated by epidermis and dermal white adipose tissue, persisting for weeks after feeding. With caloric-restriction, mouse skins thin and assimilation of circulating lipids decreases. Using multi-modal lipid profiling, keratinocytes and sebocytes are implicated in lipid changes, which correlate with thermal function. We propose that skin should be routinely included in physiological studies of lipid metabolism, given the size of the skin lipid reservoir and its adaptable functionality.